HEMATOPOIETIC PROGENITOR CELLS AS A PREDICTIVE OF CD34+ ENUMERATION PRIOR TO PERIPHERAL BLOOD STEM CELLS HARVESTING - Zulkafli, Zefarina; Mustaffa, Rapiaah; Yusoff, Shafini Mohammed (BALI MEDICAL JOURNAL, 2014)
Background: To date, the CD34+ cell enumeration has relied predominantly on flow cytometry technique. However, flow cytometry is time consuming and operator dependent. The application of the hematopoietic progenitor cells (HPCs) channel in Sysmex XE-2100, a fully automated hematology analyzer offers an alternative approach, which is with minimal sample manipulation and less operator dependent. This study evaluates the utility of HPC counts as a predictive of CD34+ enumeration prior to peripheral blood stem cells harvesting. Materials and methods: HPC, CD34+, white blood cell (WBC), reticulocytes (retic), immature platelet fraction (IPF) and immature reticulocyte fraction (IRF) were determined in 61 samples from 19 patients with hematological malignancies (15 lymphoma and 4 multiple myeloma patients) at Hospital Universiti Sains Malaysia (Hospital USM) who had received granulocyte-colony stimulating factor (G-CSF) and planned for autologous transplantation. Results: CD34+ count showed strong and significant correlation with HPC. The receiver operating characteristics (ROC) curve analysis revealed that HPC count > 21.5 x 106 / L can predicts a pre harvest CD34+ count of >20 x 106 / L with sensitivity of 77%, specificity of 64% and area under the curve (AUC) of 0.802. Conclusion: We concluded that HPC count can be a useful potential parameter in optimizing timing for CD34+ enumeration prior to leukapheresis.